2017
DOI: 10.1038/nature20817
|View full text |Cite
|
Sign up to set email alerts
|

Weak synchronization and large-scale collective oscillation in dense bacterial suspensions

Abstract: Collective oscillatory behaviour is ubiquitous in nature, having a vital role in many biological processes from embryogenesis and organ development to pace-making in neuron networks. Elucidating the mechanisms that give rise to synchronization is essential to the understanding of biological self-organization. Collective oscillations in biological multicellular systems often arise from long-range coupling mediated by diffusive chemicals, by electrochemical mechanisms, or by biomechanical interaction between cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
109
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 176 publications
(116 citation statements)
references
References 36 publications
(31 reference statements)
2
109
0
2
Order By: Relevance
“…Chen et al [41] found that with increasing bacterial concentration the velocity of E. coli within the plane exhibited a weak synchronization behavior, which lasted at least half an hour. It is interesting that the probability of quasi clockwise movement in different colonies is almost equal.…”
Section: Dynamic Assembly Behavior Of Bacteriamentioning
confidence: 99%
“…Chen et al [41] found that with increasing bacterial concentration the velocity of E. coli within the plane exhibited a weak synchronization behavior, which lasted at least half an hour. It is interesting that the probability of quasi clockwise movement in different colonies is almost equal.…”
Section: Dynamic Assembly Behavior Of Bacteriamentioning
confidence: 99%
“…Specifically, we modeled the biofilms as two coupled phase oscillators (2024) to represent their growth dynamics (fig. S3 and supplementary text).…”
mentioning
confidence: 99%
“…Swarming not only helps bacteria to colonize new niches, but has also been demonstrated to facilitate their survival on antibiotic concentrations that are lethal to the same bacteria while swimming in liquid 1519 . Dense suspensions of swimming bacteria, obtained by artificially concentrating the cells to high volume fractions, exhibit collective motion as well 2026 , but these bacteria are not equivalent to the swarm collective because swarming bacteria have an altered physiology 5,6 . How bacteria move within the swarm, if they respond to chemical gradients, and whether their motion contributes to their survival, is poorly understood compared to their swimming counterparts.…”
Section: Introductionmentioning
confidence: 99%